Catalytic enantioselective construction of axial chirality in 1,3-disubstituted allenes - Shihua Song (Nature Portfolio, 2019)
Highly enantioselective synthesis of allenes has been relying, so far, on the steric hindrance of substrates. Here the authors achieve excellent stereocontrol in the synthesis of chiral allenes with a palladium-DTBM-SEGPHOS catalytic system in a non-substrate-dependent manner.